HIV/AIDS DI KALANGAN PEKERJA SEKS PEREMPUAN Studi Kasus di Lokalisasi Kota Surabaya - Yanuar Farida Wismayanti (Puslitbangkesos Kementerian Sosial RI, 2010)
This paper based on the field research focusing at the study on women for sexual purposed. TheÂ research answer two research questions, how about the pattern of work the women for sexual purposed and how about the prevalence of spread the HIV/AIDS among of the women for sexual exploitation? This research conducted in Surabaya city, with ethnographic research approached. The result of this research indicated the women has the high risk with their activities, belong infection by the HIV / AIDS. Some sex workers, including child sex workers, ranging exposed to different types of diseases STDs (Sexually Transmitted Infections), even some of them had been infected with HIV/ AIDS. What a risk on their own bodies, they never think about it. When the women for sexual purposed was trapped in a world of prostitution, they have difficulty to get out. Crush of debt, consumer demands, including dependence on alcohol and the habit to use pills koplo every day, add a row of the reasons that make the women for sexual purposed to get out of prostitution world full of risks. The strategic for fighting back the women prostitution with HIV/AIDS needs the preventive program by campaign the HIV/AIDS and build the awareness from community, rehabilitative program by build the shelter and routine examination to sex worker and integrative programs to encourage the regulation to prevent the transmission of HIV/AIDS .